Pengaruh Konten Tiktok Terhadap Penggunaan Bahasa Indonesia Sesuai E.Y.D Di Aplikasi Whatsapp Pada Remaja Di Bandung - Fathan Nafis Ashadi; Gilang Panca Putra; Shirra Ulfi Artika; Tiara Aprilyani Salsabila (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The TikTok application has become a global phenomenon and is widely used by people of all ages, especially the younger generation, including high school teenagers. The prevalence of TikTok among Indonesian teenagers will undoubtedly affect the use of the Indonesian language in both direct and virtual communication. This study aims to investigate the influence of TikTok content on the use of proper Indonesian language, following the Enhanced Spelling System (E.Y.D), in communication through the WhatsApp application. The focus of this research is on high school students in Bandung City. The research method used is quantitative with a survey approach. Data was collected through a questionnaire created using Google Forms and distributed via the social media platform WhatsApp. The results show that the use of TikTok can influence the language used by students in communication. This study provides insights into how TikTok content affects the use of the Indonesian language among high school students. The implication is the need for a holistic approach in teaching language, including considering the influence of social media in language learning.